Variations in Aerosil concentration in Chlorpeniramin Maleat (CTM) capsule preparations on test results - Melinda Putri (Universitas STRADA Indonesia, 2019)
Capsules are solid preparations consisting of a drug in a hard or soft shell that can dissolve. (Fatmawaty, et al. 2012). Hard capsules are usually made from gelatin which consists of the capsule shell, the body and the capsule cap. The two parts of the capsule cover will cover each other when brought together and the cover will cover the body of the capsule (Ansel, 2005). Chlorpeniramin Maleat CTM) is used as an antihistamine. Antihistaminics are drugs that oppose the action of histamine on H-1 histamine receptors so they are useful in suppressing allergies caused by the appearance of symptoms due to histamine (Ansel, 1989). Antihistamines work by occupying the place in cells normally occupied by histamine, thereby eliminating histamine's ability to cause allergic reactions (Harkness, 1989). Adsorbents are substances that trap other components such as water. Aerosil is an adsorbent that is widely used in capsule preparations. Apart from having a large water absorption capability and capacity of around 50%, if dried, Aerosil will not reduce the existing water content (Lachman, 1989). The active ingredient used is CTM, where this material is hygroscopic, meaning it is able to absorb water molecules from its environment, so adsorbents are added to prevent moisture from the preparation during storage. Based on the description above, this formulation was made by varying the aerosil concentration, namely 5% (F1); 7% (F2); and 9% (F3) which is intended to observe the ability of the adsorbent as seen from hygroscopic testing of the preparation during storage. The results of this research is disintegration time on our formulations resulted in formulation 1 starting to disintegrate within 01:03 until it was completely dissolved, taking 12:02. formulation 2 started to break down within 01:40 and until everything dissolved with a duration of 12:02. The 3rd formulation started to break down within 02:05 with the total duration until it was completely dissolved was 12:58. These three formulations are in accordance with the FI standard, namely less than 30 minutes.